STUDY OF VERTEBRAL MORPHOGENESIS OF COBIA LARVAE, (Rachycentron canadum) BY DOUBLE STAINING METHODS - Afifah Nasukha; Titiek Aslianti; Agus Priyono (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2012)
Vertebral development is one of the main indicators of organism growth. The aim of this study was to know the vertebral development of cobia Rachycentron canadum in larval stage (20 day post hatch). Vertebral assay was done with double staining methods. The result showed that cobia larvae from 0 dph up to 5 dph did not have cartilage. On 5 dph up to 10 dph had pre cartilage phase composed by calcium and on 10 dph up to 18 dph were cartilage phase and marked with blue color by alcian blue. Vertebral was formed perfectly as bones on 18 dph marked with red color by alizarin red. On 20 dph, cartilage had been fully transformed to bones, and the segment of vertebral was clearly formed. Measurement showed that length of cobia vertebrae was 20.20±3.90 mm, vertebrae segment was 0.91±0.11 mm and number of vertebral segments were between 25-26 segments.